Blood and Revenge: Animal Metaphors and Nature in Macbeth and the Oresteia - Nie, Duluo (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
Renowned classicist Gilbert Murray has made compelling arguments about the connection between Aeschylus and Shakespeare in his famous essay Hamlet and Orestes: A Study in Traditional Types. Through a close reading of the Oresteia and Macbeth, it is not difficult to find that the latter play, to some extent, is an intentioned “translation” and “rewriting” of the great theatrical tradition of the Attic tragedy, especially that represented by Aeschylus. The dramatic elements inviting such a comparative reading, among many other things, include the motif of bloodstained hands, masculine queens, sleeplessness and dream terrors, and most important of all, the mechanism of blood-shedding and revenge. This paper discusses their affinity through the lens of allusions to birds, and animals, inversion of the established order, and its final restoration to reveal Macbeth as a play that is fundamentally concerned with the classical theme of blood-shedding and revenge with its borrowing of multiple dramatic techniques.